Pemanfaatan Ekstrak Daun Miana (Coleus Scutellarioides (L) Benth) Menggunakan Metode Ultrasonic Asisted Extraction Untuk Identifikasi Formalin Pada Mie Basah - Rismawaty Sikanna; Muliyani; Arfiani nur (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2023)
Miana (Coleus scutellarioides (L) Benth.) leaves contain anthocyanin compounds that can be used to detect formalin in food, including wet noodles. The purpose of this study was to determine the highest levels of anthocyanin extract of miana leaves produced using the ultrasonic assisted extraction (UAE) method with variations in extration time and to determine the potential of miana leaf anthocyanin compounds in detecting formaldehyde content in wet noodles. The extraction method used is UAE with 5 variations of extraction time. Anthocyanin levels were measured using a UV-VIS Spectrophotometer at wavelengths of 510 and 700 nm using differential pH, namely pH 1 and pH 4.5. Formalin identification was carried out on wet noodles with the concentration of 0.25; 0.5; 1; and 2 ppm. The results obtained the highest level of anthocyanin in miana leaves, namely 196,66 mg/L wich was extracted for 10 minutes wich could be used for identification of formalin in wet noodles. Keywords: Miana leaf (Coleus scutellarioides (L) Benth.), Ultrasonic Assisted Extraction (UAE), Anthocyanin and Formaldehyde